APPLYING PANEL DATA MODEL FOR COMPARING STATIC AND DYNAMIC FORECASTS OF AN AUTOREGRESSIVE MONEY DEMAND INCORPORATING FINANCIAL INNOVATION IN ASEAN COUNTRIES - Payam Mohammad Aliha; Associate Professor Dr. Tamat Sarmidi; Dr. Fathin Faizah Said (International Journal of Accounting, Finance and Business, 2020)
This paper investigates the impact of financial innovations on the demand for money using a dynamic panel data for 10 ASEAN member states from 2004 to 2012 and attempt to forecast the demand for money during 2013 â€“ 2016 to compare between forecasting performance of the fixed effects model with that of random effects model and also to compare the forecasting accuracy of dynamic forecasting and static forecasting obtained from these two models. An autoregressive model by definition is when a value from a time series is regressed on previous values from that same time series. There are two types of forecasting namely dynamic forecast and static forecast. â€œDynamic forecast will take previously forecasted values while static forecast will take actual values to make next step forecast. Panel effects models assist in controlling for unobserved heterogeneity when this heterogeneity is constant over time and correlated (fixed effects) or uncorrelated (random effects) with independent variables. Hausman test indicates that the random effects model is appropriate. We use the conventional money demand that is enriched with the number of automated teller machines (ATM) to proxy for the effect of financial innovations on money demand. By comparing the magnitude of â€œRoot Mean Squared Errorâ€ (RMSE) as benchmark for the two forecasts (0.1164 for dynamic forecast versus 0.0635 for static forecast) we simply find out that static forecast is superior to dynamic forecast meaning that static forecast provides more accurate forecast compared to dynamic forecast for fixed effects model. Therefore, we conclude the static forecast on the basis of random effects model provides the most accurate forecasting. The estimation result of the chosen random effects regression also indicates the estimated coefficient of ATM is not significant meaning that ATM does not impact money demand in ASEAN countries.